An experiential perspective on uncertainty in peer-to-peer platform services - Lopez, Raul Perez; Yrjölä, Mika; Becker, Larissa; Panina, Ekaterina; Saarijärvi, Hannu (Emerald, 2025)
Purpose The rapid growth of digital peer-to-peer (P2P) platforms has contributed to increased circular consumption characterized by high consumer uncertainty, which in turn affects consumer attitudes and behaviors. However, research has addressed uncertainty in platform services through a narrow conceptualization that neglects its experiential nature. Thus, this study develops an experiential perspective on uncertainty in platform services.
Design/methodology/approach The authors collected data on consumers' experiences with P2P platform services through focus groups and in-depth interviews. The data were interpreted by applying customer experience as a conceptual lens, following the principles of enabled theorizing and systematic combining.
Findings The study conceptualizes "uncertainty" in P2P platforms through an experiential perspective, shedding light on its multidimensional and experiential nature, the diverse stimuli that trigger the uncertainty experience, and consumer's strategies to manage it.
Originality/value This research contributes to the literature on platform services and customer experience by offering an alternative experiential perspective to conceptualize uncertainty in P2P platforms, thus shedding light on several unaddressed aspects of this phenomenon.